ANALISIS TINGKAT KEMATANGAN BUDAYA KESELAMATAN KERJA PADA PROYEK KONSTRUKSI MIGAS NASIONAL - Puruboyo, Sakti; Djunaidi, Zulkifli (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2023)
This study analyzes the maturity level of work safety culture in oil and gas construction projects at PT. XYZ. The research was conducted during 2022 using questionnaire survey data. The number of respondents who were conducted in this study amounted to 675 with various kinds of positions, work experience, and others. In measuring work safety culture, there are three dimensions, namely: transformational leadership, transactional leadership, and safety climate. The results of this study indicate that three dimensions have an average value with a "calculative" level which is in the early stages towards a proactive culture of safety. This study aims to provide insight to project management to improve safety culture in the oil and gas project area. Improvement of safety can be done by analyzing risks where oil and gas projects have a very high level of risk. Therefore, prioritizing work safety will reduce the number and risk of workers taking unsafe actions so as to reduce the number of incidents in The Project Area.